Peran Budaya dalam Pembentukan Identitas Manusia - Rio Febrian; Muhammad Fajrul Islam; Purnama Yudistira (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Human identity is a complex and dynamic concept, formed through interactions within society and influenced by various factors, with culture as the main element in its formation. Culture includes outward elements such as language, clothing, and food, as well as values, norms, and belief systems that shape an individual's outlook on life and behavior. The process of cultural socialization that begins at birth through family, education and mass media plays an important role in shaping one's identity, both individually and collectively. This research aims to explore the role of culture in the formation of human identity, focusing on the influence of local and global cultures and cultural elements such as language, religion, and cultural symbols. The method used is a qualitative approach with a literature study, which collects data from written sources, including journal articles and books, to examine the relationship between culture and identity. The results show that culture has a fundamental role in shaping human identity, with cultural socialization as the main process in internalizing values and norms that shape behavior and outlook on life. In addition, globalization affects the dynamics of identity, creating the phenomenon of hybrid identities that reflect the fusion of local and global cultures.